2010
DOI: 10.1371/journal.pone.0012639
|View full text |Cite
|
Sign up to set email alerts
|

Nucleo-Cytoplasmic Localization Domains Regulate Krüppel-Like Factor 6 (KLF6) Protein Stability and Tumor Suppressor Function

Abstract: BackgroundThe tumor suppressor KLF6 and its oncogenic cytoplasmic splice variant KLF6-SV1 represent a paradigm in cancer biology in that their antagonistic cancer functions are encoded within the same gene. As a consequence of splicing, KLF6-SV1 loses both the C-terminus C2H2 three zinc finger (ZF) domain, which characterizes all KLF proteins, as well as the adjacent 5′ basic region (5BR), a putative nuclear localization signal (NLS). It has been hypothesized that this NLS is a functional domain critical to di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Expression of KLF7 in cultured neurons was not increased by using smaller epitope tags, such as Flag or myc, or by attaching tags to the C terminus, suggesting that poor expression of KLF7 was not an artifact of tag size or location. Other KLF family members are subject to rapid degradation under the control of posttranslational modifications and protein-protein interactions; notably, the stability of both KLF5 and of KLF6 (which has high sequence homology to KLF7) is increased by deleting N-terminal motifs (28,29). We found that deletion of the KLF7 N terminus, a previously identified 76-aa acidic transactivation domain, increased KLF7 expression more than threefold (Fig.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Expression of KLF7 in cultured neurons was not increased by using smaller epitope tags, such as Flag or myc, or by attaching tags to the C terminus, suggesting that poor expression of KLF7 was not an artifact of tag size or location. Other KLF family members are subject to rapid degradation under the control of posttranslational modifications and protein-protein interactions; notably, the stability of both KLF5 and of KLF6 (which has high sequence homology to KLF7) is increased by deleting N-terminal motifs (28,29). We found that deletion of the KLF7 N terminus, a previously identified 76-aa acidic transactivation domain, increased KLF7 expression more than threefold (Fig.…”
Section: Resultsmentioning
confidence: 58%
“…The fact that two evolutionarily divergent domains, with well-characterized and opposite effects on transcription, give opposite effects on neurite outgrowth when fused to KLF7's DNA binding domain strongly favors transcriptional activation as KLF7's mechanism of action. Second, N-terminal sequences keep expression low in neurons even after attempted overexpression, possibly by targeting KLF7 protein for degradation (28,29). We developed VP16-KLF7 as a means to enhance expression, but cannot rule out the possibility that VP16-KLF7 could activate nonphysiological targets, which would confound conclusions regarding endogenous KLF7.…”
Section: Slices Aged 8 DIV and Treated With Aav8-vp16-klf7 (E-h) Showmentioning
confidence: 99%
“…XPO1 overexpression has been suggested to be a general feature of cellular transformation (9) and has been observed in a number of hematologic and solid tumors (9-13), including ovarian cancer (10). Most relevant to this study, XPO1 is the only known transporter for a number of well-characterized ovarian cancerassociated proteins, including p53 (11)(12), BRCA1 (13), IkBa (14), KLF6 (15), sequestosome 1 (SQSTM1; also known as p62), and PP2A (CIP2A) (16), all of which play roles in ovarian cancer initiation, cell-cycle progression, the DNA damage response, apoptosis, autophagy, and chemoresistance. Therefore, XPO1 seems an excellent ovarian cancer therapeutic target.…”
Section: Introductionmentioning
confidence: 93%
“…4C). It has been reported that KLF6 shuttles between the cytoplasm and nucleus (24). We thus performed cellular fractionation assays to isolate the cytosol and nuclear fractions and examined whether KLF6 interacts with p65 in the nucleus or cytoplasm by coimmunoprecipitation.…”
Section: Klf6 Is Dispensable For Tnf␣-and Il-1␤-triggered Nuclear Tramentioning
confidence: 99%